2007
DOI: 10.1007/s00381-007-0422-6
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological screening of a group of preterm twins: comparison with singletons

Abstract: The twins' neuropsychological outcome was not more marked than that of the singletons. Birth weight discordance and chorionicity were the only predictive perinatal factors with worse outcome in the twin population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…In terms of cognitive performance, results are mixed. One study suggested that MC twins have higher rates of pathological nonverbal performance and learning disabilities (Einaudi et al 2008 ), whereas other studies showed no difference in mental development indexes (e.g., on the Bayley; Welch et al 1978 ; Steingass et al 2013 ). Studies examining cerebral palsy are inconsistent, with some suggesting that MC twins are at a higher risk (Burguet et al 1995 , 1999 ), but others finding no difference in prevalence of cerebral palsy in MC versus DC twins (Steingass et al 2013 ; Hack et al 2009 ), or that the association was attenuated when controlling on other perinatal factors (Livinec et al 2005 ).…”
Section: Resultsmentioning
confidence: 99%
“…In terms of cognitive performance, results are mixed. One study suggested that MC twins have higher rates of pathological nonverbal performance and learning disabilities (Einaudi et al 2008 ), whereas other studies showed no difference in mental development indexes (e.g., on the Bayley; Welch et al 1978 ; Steingass et al 2013 ). Studies examining cerebral palsy are inconsistent, with some suggesting that MC twins are at a higher risk (Burguet et al 1995 , 1999 ), but others finding no difference in prevalence of cerebral palsy in MC versus DC twins (Steingass et al 2013 ; Hack et al 2009 ), or that the association was attenuated when controlling on other perinatal factors (Livinec et al 2005 ).…”
Section: Resultsmentioning
confidence: 99%
“…MC and twin birth weight discordance are the only variables associated to a higher prevalence of language delay, cognitive and attention deficit at the age of 4 years [30]. MC twins, especially if born prematurely and sIUGR, are at a higher risk not only of major neurological sequelae such as CP and neurosensory deficits, but also of minor neurodevelopmental sequelae, potentially leading to future academic and social integration difficulties.…”
Section: Neurodevelopmental Outcomesmentioning
confidence: 99%
“…From many cohorts and case studies it appears that during early childhood, the cognitive skills of twins are influenced by GA, birth weight and the zygosity-chorionicity status of the pregnancy [39,71,72] . Towards adulthood, genetic and environmental factors become more pronounced.…”
Section: Cognitive Outcome In Multiplesmentioning
confidence: 99%